2000
DOI: 10.1007/s001010050005
|View full text |Cite
|
Sign up to set email alerts
|

Koronarsinusdilatation

Abstract: A 36-year old woman was presented to our hospital with congenital ventricular septal defect and one-vessel coronary artery disease (75% proximal left main coronary artery) for CABG and repair of the VSD. After induction, a transesophageal echocardiographic (TEE) baseline examination was performed, showing a severely dilated coronary sinus (CS) measuring approximately 3 cm (abnormal >1 cm). We suggested a persistent left superior vena cava (PLSVC) draining into the CS. PLSVC is a common venous congenital anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A dilated CS can result from increased blood flow due to abnormal venous drainage in the left superior vena cava, total anomalous intra-cardiac pulmonary venous drainage, severe tricuspid regurgitation, CS diverticulum, or a coronary artery to CS fistula. The absence of primary abnormalities is generally a manifestation of high RA pressure due to functional tricuspid regurgitation (10-12). Koberstein et al (13) showed that CS dilatation with RA blood reflux to the CS was due to increased RA pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A dilated CS can result from increased blood flow due to abnormal venous drainage in the left superior vena cava, total anomalous intra-cardiac pulmonary venous drainage, severe tricuspid regurgitation, CS diverticulum, or a coronary artery to CS fistula. The absence of primary abnormalities is generally a manifestation of high RA pressure due to functional tricuspid regurgitation (10-12). Koberstein et al (13) showed that CS dilatation with RA blood reflux to the CS was due to increased RA pressure.…”
Section: Discussionmentioning
confidence: 99%